Ojcowie i synowie w deklamacji rzymskiej (Roman Declamations on Fathers and Sons) - Sapota, Tomasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2015)
The text outlines how the concept of pietas understood as unreserved reverence of sons towards their fathers was incorporated into the repertory of school declamations that in the Roman education system made the main means of modelling the social attitudes of younger generations.